Determinants of Economic Growth: The Role Of Poverty, Unemployment, and HDI (2019–2024) - Rebecca Cindy Sartika; Muh. Syaiful Bakhri; Firdan Thoriq Faza (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Indonesia is committed to achieving the Sustainable Development Goals (SDGs), which necessitates continuous evaluation of development outcomes across regions. Economic growth serves as a key indicator of sustainable development, making it essential to understand the factors that influence it. This study aims to examine the impact of the poverty rate, unemployment rate, and Human Development Index (HDI) on economic growth in Central Java Province. Employing a quantitative approach, the research utilizes panel data from 35 regencies and municipalities in Central Java for the 2019 to 2024 period and applies panel data regression using the Fixed Effect Model (FEM), selected through specification tests to ensure robustness. The findings reveal that poverty (β = -0.0149967; p < 0.001) and unemployment rates (β = -0.0051182; p < 0.001) have a negative effect on economic growth, while the HDI (β = 3.201663; p < 0.001) has a positive and significant effect. The model explains approximately 60% of the variation in economic growth (R² = 0.6019). These results underscore the importance of reducing poverty and unemployment while enhancing human development as key drivers of regional growth. The study contributes empirically by integrating poverty, unemployment, and human development variables simultaneously within the SDG framework, thereby providing comprehensive insights to support policy formulation aimed at achieving inclusive and sustainable economic growth in Indonesia.